Development perspectives for the City of Hamburg: Migration, commuting, and specialization - Amelie Boje; Ingrid Ott; Silvia Stiller (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
This paper disentangles the single effects of increasing transportation costs on the arising economic structure and applies them to the regional level of the metropolis of Hamburg. Therefore we begin with a general indexing of the metropolis Hamburg in the context of Germany's ten biggest cities according to some key economic variables. Of major importance are issues of migration, commuting as well as structural change and regional specialization. As will become apparent all these aspects are differently affected by (changing) transportation costs and it is finally the interplay of different forces that shapes the future structure and hence the economic success of the metropolis. From the viewpoint of private individuals, increasing transportation costs affect the outweighing of commuting from home to the working place versus migration. Focusing on the production site, not only direct but also indirect effects that arise from horizontal or vertical relationships gain importance.
Keywords: 330